Clinical application of common inflammatory and nutritional indicators before treatment in prognosis evaluation of non-small cell lung cancer: a retrospective real-world study - Lv, Xiang; Xu, Bin; Zou, Qingxia; Han, Songtao; Feng, Yangchun (Frontiers in Medicine, 2023)
Objective: To evaluate the prognostic value of common clinical inflammatory and nutritional indicators before treatment in patients with non-small cell lung cancer in the real world. Method: A total of 5239 patients with pathologically confirmed non-small cell lung cancer from 2011 to 2018 in the Affiliated Cancer Hospital of Xinjiang Medical University were collected, and their inflammatory and nutritional indicators before treatment were collected, of which a total of 1049 patients randomly sampled from 18% to 20% of patients each year were used as the validation set, and the remaining 4190 patients were used as the validation set.According to the 8th edition of the guidelines for the diagnosis ,treatment and stage risk stratification of lung cancer, the patients were divided into four groups: stage I/II operable, stage III operable, stage III inoperable and stage IV. X-tile software was used to intercept and classify the cut-off values of each index in the validation set. Univariate and multivariate Cox proportional -hazard regression were used to screen the independent risk factors affecting the prognosis of non-small cell lung cancer and establish a prognostic model for 1 year, 3 years and 5 years. The validation set was used to verify its performance. Finally, K-M curve was used to assess the survival rate, and the corresponding nomogram was established for clinical use. Results: After screening, no effective indicators were found in the stage I/II operable group, RDW and CA125 were effective indicators in the stage III operable group , CYRFA21-1 and CA125 were effective prognostic indicators in the stage III inoperable group , and CYRFA21-1, CA125, NLR and α1-globulin were effective indicators of prognosis in the stage IV. The model was constructed with the best validation power in Stage IV patients . Conclusion: For patients with stage III and IV non-small cell lung cancer, some inflammatory markers, serum tumor markers and nutritional indicators are independent prognostic factors. Combined with the general data of patients, the constructed prognostic evaluation model has the best efficacy in patients with stage IV and can be widely used in clinical practice.